Prochelator tupuhi sp. nov., the first record of Desmosomatidae Sars, 1897 (Crustacea: Isopoda) from New Zealand waters - Brix, Saskia; Bruce, Niel L. (Zootaxa, 2008)
Prochelator tupuhi sp. nov. is the first record of the genus Prochelator Hessler, 1970 from Southern Hemisphere waters, and the first record of the family Desmosomatidae from New Zealand. The new species can be distinguished from all other species of the genus by the following characters: body elongate, without spine-like ventral elongations on pereonites 1–4, pereonite 1 as high as pereonite 5, mesial lobe of the maxilla much shorter than in the other species of the genus, reaching only half the length of the lateral lobe, carpus of pereopod 1 distinctly produced at the base of the claw, propodus broadest at the articulation to the carpus, tapering distally.